GELS FOR ORAL ADMINISTRATION. PART 1. MEDICAL PRODUCTS AND DIETARY SUPPLEMENTS (REVIEW) - E. Y. Zagorulko; A. A. Teslev (Разработка и регистрация лекарственных средств, 2019)
The characteristics of gels for oral administration as a dosage form have been considered in the article. A review of medical products and dietary supplements in the form of gels for oral administration available on the Russian market has been presented.